Angiopoietins/TIE2 system and VEGF are involved in ovarian function in a DHEA rat model of Polycystic Ovary Syndrome - Abramovich, Dalhia Nurit (2012)
Polycystic ovary syndrome (PCOS) is the most common endocrinological pathology among women of reproductive age. It is characterized by anovulation, oligo- or amenorrhea, hyperandrogenism, obesity, and insulin resistance. PCOS patients present with elevated levels of vascular endothelial growth factor (VEGF) in serum and follicular fluid. In this study, we examined the ovarian expression of angiopoietins (ANGPT) and their receptor tyrosine kinase receptor (TIE2), involved in the stabilization of blood vessels, in a rat model of dehydroepiandrosterone-induced PCOS. We also analyzed the effect of ovarian VEGF inhibition on ANGPT/TIE2, follicular development, and vascular stability. VEGF levels were increased in the PCOS ovaries, whereas the levels of its receptor fetal liver kinase-1 were decreased. In addition, the periendothelial cell area and the ANGPT1 to ANGPT2 ratio in the ovary were increased in the PCOS group. Percentage of primary follicles was increased and the percentage of preantral follicles and corpora lutea was decreased in the PCOS group. VEGF inhibition decreased the percentage of primary follicles close to control values. Interestingly, despite the presence of cysts in the ovaries from VEGF inhibitor-treated PCOS rats, its percentage was lower than the PCOS group without treatment. In summary, this study describes an alteration not only in the VEGF/fetal liver kinase-1 system but also in the ANGPT/TIE2 system in a dehydroepiandrosterone-induced PCOS rat model. This leads to an increase in periendothelial cell recruitment. We also demonstrated that ovarian VEGF inhibition can partially restore the accumulation of small follicles in PCOS rats and reduces cyst formation, improving ovulation and follicular development. Therefore, the inhibition of VEGF could be considered, in addition to other currently applied treatments, as a new strategy to be studied in PCOS patients to restore ovarian function.